BLACK ATHEIST: ASPECTS OF COMMUNISM IN LANGSTON HUGHES'S SELECTED POEMS - Ali Kareem Sameer; Hasan Hadi Ali, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This paper aims to study the perspectives of communism as a dogma in Langston Hughes's selected poems. Hughes was an African American poet who observed communism as an outlet for his problems and suffering under the social prejudice of whites. He reflected the impact of discrimination in part of the race and social segregation in most of his poems. Hughes embedded communist aspects in some of his poems like Good-Bye Christ, as an outcome of the recurrence of the daily conducts of discrimination and racism against Afro-Americans. Thus, this paper is conducted in the light of “Speaking out for Justice” to denote the injustice situations of the dark-skinned people via adopting atheism in an idealized society, America. Some questions will be articulated to uncover the ideology of Hughes in discussing his issue as such how did Hughes reflect communist trends and religious tensions in his poetry?